JAPANESE TYPOGRAPHY ESSENTIALS: LEARNING FRAMEWORK OF TYPOGRAPHY IN JAPAN (Japanese Typography as a Visual Form of Japanese Writing) - Limantoro, Gray Hansen (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
This research discusses the comparison of designs that use typography or not. With three types of Japanese fonts representing the gothic, Mincho, and calligraphy categories, namely DFMincho-SU, Yu Mincho, and BIZ UDGothic. The purpose of this study is to look at the differences in typographic characteristics of each font and their influence on Japanese writing. The methods used included font sampling and a comparative study in which each font was typed on two different sheets: one without typographic manipulation and one with typography applied at the same size. Japanese writing is closely tied to typography because of the emotional value in characters. Calligraphic Japanese fonts are expressive and aesthetically pleasing. Japanese typography enhances visual design within writing rules. The development of Japanese language learning, especially in writing, can benefit from Japanese typography as a visual tool.